Determinants of Environmental Degradation and Empirical Investigation of Kuznets Curve: A Comparative Study of India and Bangladesh - Husain, Humaira (Asian Journal of Empirical Research, 2016)
This paper investigates the factors responsible for Environmental degradation in terms of higher Carbon dioxide and Nitrous oxide emission over the period 1981 – 2011 for Bangladesh and India from data of World development indicator. Industrialization and greenhouse gas are major contributing factors identified for deteriorating the air quality in Bangladesh and India respectively. Concentration of population in urban areas increases carbon emission and economic globalization reduces Nitrous oxide emission in both economies. Estimation results of reduced from equation for CO2 emission provides support in favour of inverted U and N shaped Kuznets curve for India which is robust to using dynamic specification. For Bangladesh the shape is Inverted U but this is not robust to using dynamic model. In quadratic approach to Kuznets curve energy consumption does play an important role for increased carbon emission in India but not in Bangladesh.